Biphasic changes in the density of muscarinic and beta-adrenergic receptors in cardiac atria of rats treated with diisopropylfluorophosphate - Myslivecek, J; Trojan, S; Tucek, S (Life sciences, 1996)
Chronic treatment with organophosphate inhibitors of cholinesterases is known to bring about down-regulation of muscarinic acetylcholine receptors in the heart while its effect on the functionally antagonistic beta-adrenergic receptors is not known. We describe experiments in which rats were exposed to daily injections of diisopropylflurophosphate (DFP) and the density of muscarinic and beta-adrenergic binding sites in their cardiac atria was measured according to the binding of (3H)quinuclidinyl benzilate ((3H)QNB) and (-)-4-(3-tert-butylamino-2-hydroxy)-propoxy-(5,7-3H) benzimidazol-2-one ((3H)CGP 12177) as subtype non-specific muscarinic and beta-adrenergic ligands, respectively. Biphasic course of changes was discovered with both ligands. With the dosage scheme applied, the density of beta-adrenoceptors was augmented 24 h after the first dose of DFP and decreased to about one half of control values after 5 days of treatment with DFP. The density of muscarinic receptors was augmented after two days of treatment with DFP and decreased to about one half of control values after 5 days of treatment. Comparatively small changes in the heart rate were observed during the treatment, they reflected changes in the muscarinic and beta-adrenergic receptor density. The finding of DFP-induced changes in the binding of (3H)CGP 12177 suggests that the mechanisms responsible for the control of the density of muscarinic and beta-adrenergic receptors in the heart cells are interconnected but potential roles of other factors involved in in vivo experiments deserve further analysis. The transient increase in the density of muscarinic receptors after two days of DFP treatment appears related to published data on transient stimulation by cholinergic agonists of the transcription of mRNAs for muscarinic receptors.
Keywords: Receptors, Adrenergic, beta; Cholinesterase Inhibitors; beta-adrenergní receptory; Male; Rats, Wistar; receptory muskarinové; srdce; isofluorofát; Heart Rate; Isoflurophate; Propanolamines; mužské pohlaví; srdeční frekvence; potkani Wistar; chinuklidinylbenzilát; krysa rodu Rattus; Animals; propanolaminy; zvířata; Rats; Receptors, Muscarinic; Heart; cholinesterasové inhibitory; Quinuclidinyl Benzilate